Examination of Secondary Students' Visual Images about Climate Change - Melehat Gezer (Journal of Education in Science, Environment and Health)
In this study, it was aimed to examine the perceptions of secondary school students about climate change. The study was planned according to the phenomenological design. The research was carried out with the participation of 131 students selected according to the criterion sampling. Students were asked to draw pictures about climate change and the collected pictures were subjected to content analysis. Since 12 of the pictures could not be evaluated under any theme, they were excluded from the data set and coding were done on 119 drawings. As a result of the data analysis, three themes were determined as temperature increase and its effects, change in thermal and precipitation regime, and extreme weather events. Under these three themes, subcategories were created based on the drawings that were similar to each other. As a result of the research, it has been determined that secondary school students have a high awareness of climate-related events and the directly observable effects of climate change in the city they live in.